PEMANFAATAN SISTEM INFORMASI DI RUMAH SAKIT TK.II dr.SOEDJONO MAGELANG - , Lilis Mawati, Agastya, SE., MBA., MPM. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background : The hospital as an organization that involves multiple Installation requires information systems that can provide quick and accurate information to both management and the public service users. Dr.Soedjono Tk.II Hospital as one of the computer users in information systems. Unfortunately, computer-based information systems are not used according to its function. Researchers want to try to figure out the cause of non-functioning information systems. Objective : How does use of information systems in improving health services in hospitals Tk.II dr.Soedjono the efficiency, effectiveness, communication, collaboration and competitive power. Method : The study was descriptive with cross section data. Data were analyzed using the Likert Scale 5 levels of scale (1) "strongly disagree up to a scale (5)" strongly agree. The research instrument used questionnaires and in-depth interviews using open questions related to the factors that affect the application of information systems technology. Results and Discussion : Overall the results obtained for the use of information systems for efficiency, effectiveness, communication, collaboration and competitive power show good results on average in terms of value of each 50 to 90%. Conclusion and recommendation : Hope hospital with a head of this research, the establishment of good cooperation between doctors, nurses and patients as well as the role of information systems are not the duties and responsibilities overlap. Similarly, the data processor is expected to carry out their duties properly, skilled, optimal and timely.